Let a 1 = 1 , a 2 = 1 and the recurrence relation is a n = a n − 2 a n − 1 2 + 2 , ∀ n ≥ 3 . then a n is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution
a 1 = 1 and a 2 = 1
we calculate a 3 and a 4 and find them to be 3,11 respectively
now let us assume a k is an integer
so a k − 2 ( a k − 1 ) 2 + 2 is an integer
now a k + 1 = a k − 1 ( a k ) 2 + 2
putting value of a k we get
a k + 1 = a k − 1 ( a k − 2 ( a k − 1 ) 2 + 2 ) 2 + 2
solving it(openig the square and adding) we see that for it to be an integer a k − 1 must divide 2 ( a k − 2 ) 2 + 4
so a k − 1 ( a k − 2 ) 2 + 4 must be an integer
putting value for a k − 1 we get
( a k − 2 ) 2 + 2 ( 2 ( a k − 2 ) 2 + 4 ) × ( a k − 3 )
which is an integer if and only if a k − 3 is an integer
now by induction : if p(k+1) is true only when p(k) and p(k-3) are true and p is true for first four natural numbers then it true for all natural numbers
and we have already done that hence the sequence returns only integer values.
Nice solution
Problem Loading...
Note Loading...
Set Loading...
by rearranging terms we get a n × a n − 2 = a n 2 + 2 . replace n by n − 1 we get a n + 1 × a n − 1 = a n 2 . subtract and trivial transformation yields a n a n + 1 + a n − 1 = a n − 1 a n + a n − 2 = c . Substituting the initial conditions a 1 = a 2 = 1 we get c = 4 . therefore we get a n + 1 = 4 a n − a n − 1 . by induction we can show a n is always integers.